Penerapan Prinsip Lean Manufacturing untuk Efisiensi Operasional dan Produktivitas: Tinjauan Literatur - Aulia Rizka; Masduki Asbari; Rudi Agus Setiawan (Yayasan Aya Sophia Indonesia, 2024)
Technological developments and globalization have increased the level of competition in the manufacturing sector. To be able to compate and survive in a competitive business environment, manufacturing companies need to meet customer satiscfaction by increasing productivity and efficiency in their operations, one of which is by implementing lean manufacturing. The aim of this research is to determine the effect of implementing lean manufacturing on increasing productivit in manufacturing companies. This reseach uses a literature review method in the form of a literature review study. Researchers obained scientific articles to research from the result of the Google Scholar and Academia.edu research libraries. The number of scientific articles examined in tis literature was six scientific articles. From the researchers’s findings, the application of lean manufacturing has significant influence on reducing waste increasing productivity and production efficiency in manufacturing companies.